2006
DOI: 10.1080/09513590600604541
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in women with polycystic ovary syndrome: A comparison with the general population using the Polycystic Ovary Syndrome Questionnaire (PCOSQ) and the Short Form-36 (SF-36)

Abstract: PCOS has a negative impact on HRQoL even when compared with other serious health conditions. The PCOSQ is reliable and valid for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
143
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(161 citation statements)
references
References 22 publications
14
143
2
2
Order By: Relevance
“…Due to the complicated treatments and high levels of stress, infertility has become a feature of chronic physical illness 10 . Other studies have confirmed the reduced quality of life after infertility 11,12 .…”
Section: Discussionmentioning
confidence: 64%
“…Due to the complicated treatments and high levels of stress, infertility has become a feature of chronic physical illness 10 . Other studies have confirmed the reduced quality of life after infertility 11,12 .…”
Section: Discussionmentioning
confidence: 64%
“…Results of the current study demonstrated that consequences of excess weight on the physical aspects of HRQOL varied between women with PCOS and healthy controls, results in agreement with those of a study that reported co morbidity of obesity had a greater impact on HRQOL. 15 With early diagnosis and adequate information, individuals can prevent serious complications and minimize the distressing symptoms that accompany PCOS. However, in this index study there was no difference were found in lower QoL in between longer and shorter duration of illness (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al [5] found emotional and social functioning more affected than the areas of physical functioning. In the study by Coffey et al [8], women with PCOS had a lower health-related quality of life than patients suffering from asthma, epilepsy, diabetes or back pain. The prevalence of anxiety and depressive symptoms in patients with PCOS was also higher than in the general population of women [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%